On the Melodic Nature of Lad Combinations in Traditional Music - Muminova Dilfuzakhon Numonovna (Researchparks Publishing, 2021)
structures of curtains the essence of the melody of curtain combinations in music, the theory of intervals are highlighted. In the works of Abdurahman Jami's